DIVERSIDADE E REDES DE INTERAÇÃO DE ABELHAS VISITANTES FLORAIS DA PITANGUEIRA (Eugenia uniflora L., MYRTACEAE) EM FRAGMENTOS DE FLORESTA OMBRÓFILA MISTA NO MUNICÍPIO DE GUARAPUAVA, PR - Diniz, Mary Ellen dos Reis (2014)
Eugenia uniflora belongs to the Myrtaceae family. This genus is the most diverse among the Angiosperms the Atlantic Forest biome, which has several forest formations, including the Araucaria Moist Forest, which currently is fragmented. Pollination in Myrtaceae occurs primarily by bees. Pollen analysis allows knowledge of the history of visitation of bees and is a complementary tool in the study of interactions between bees and flowers. Studies about interaction networks have aided in understand of the dynamics of mutualistic relationships. The objective of this study was investigate the diversity of bee pollinators of E. uniflora and the relationship of bees with their flowers. This study was performed in two areas located in Guarapuava, PR, Southern Brazil. Diversity of bees, indices of consistency and dominance of species and abiotic variables and correlation between activity of bees were calculated. All the pollen material from the body of bees and plants found nearby was subjected to acetolysis process. The flowering period was from August 25?? until September 14th 2012. Anthesis of the E. uniflora starts around 5:30 a.m. and the flowers last one day. Were obtained 826 bees, of the 39 species and four families, with the highest family Halictidae richness (N= 23 ), followed by Apidae (N= 11), Colletidae (N= 4) and Andrenidae (N= 1). Apis mellifera was the only common and most abundant species (N= 337 ), followed by Scaptotrigona bipunctata (N= 293) and Melipona obscurior (N= 74). Seven species were classified as intermediate and 31 species were classified as rare. Was obtained a larger number of flower visiting bees in times at 10:00 a.m. and 11 a.m. There was a correlation between activity of bees and abiotic variables. Were obtained 29 species of bee with pollen load and 20 pollen types. All the bees present generalist habits and E. uniflora was the one who interacted with all species of bee. Apis mellifera was the most generalist specie. The networks obtained are nested, with low specialization and there is strong interaction of bees with E. uniflora, which reveals that your flowers are an important funding pollen for bees who visit.